Nanocoating of Al2O3 additive on ZrO2 powder and its effect on the sintering behaviour in ZrO2 ceramic - Goncalves, R. F.; Godinho, M. J.; Leite, E. R.; Maciel, A. P.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer, 2007)
ZrO2 powder was coated with Al2O3 precursor generated by a polymeric precursor method in aqueous solution. The system of nanocoated particles formed a core shell-like structure in which the particle is the core and the nanocoating (additive) is the shell. A new approach is reported in order to control the superficial mass transport and the exaggerated grain growth during the sintering of zirconia powder. Transmission electron microscopy (TEM) observations clearly showed the formation of an alumina layer on the surface of the zirconia particles. This layer modifies the sintering process and retards the maximum shrinkage temperature of the pure zirconia.